Eksplorasi Etnomatematika pada Menara Rumah Budaya Sumba dan Penerapannya dalam Pembelajaran Matematika - Ngongo, Dorkas; Malo, Verena; Lede, Yulius Keremata (Indo-MathEdu Intellectuals Journal, 2026)
The sumba cultural house tower is a special museum used to introduce the history and culture of sumba. The purpose of this study is to determine the mathematical aspects and their application in mathematics found in the sumba cultural house tower in southwest sumba regency. This study uses a descriptive qualitative approacch with an ethnographic research type. The data analysis technique used is thematic analysis. This study was conducted by interviewing one of the guest reception figures at the sumba cultural house and simultaneously with documentation to obtain real data. The interview data is in the form of an analysis of the sumba cultural house tower in southwest sumba regency which is then examined for mathematical aspects based on several activities. The sumba cultural house tower as a whole has geometric elements, namely an isosceles triangle, an isosceles trapezoid, an upper trapezoid, and a lower trapezoid